PELATIHAN PENGGUNAAN CRAB BOX PADA PEMBESARAN KEPITING BAKAU DESA KAJUARA KABUPATEN BONE: Training On The Use Of Crab Box On Mud Crab Enlargement In Kajuara Village Bone Regency - Nurul Eka Wijayanti Risa; Aam Azatil Isma; Andi Panca Wahyuni (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The method of cultivating mud crabs in Kajuara Village is still carried out traditionally and uses natural food, thus affecting the production of crabs which are not uniform in terms of size and weight. Apart from that, there is still a lack of partner knowledge regarding the behavior and habits of mud crabs as well as appropriate methods for cultivating mud crabs. The aim of this service is to increase the knowledge and skills of cultivators in cultivating mud crabs using crab boxes. The stages of implementing service activities include: 1) Survey and interview stage, 2) preparation stage, 3) implementation stage and 4) evaluation stage. Based on the achievements of the service activities, participants have knowledge and skills in the mud crab cultivation method using a crab box.